Louis Kahn in Tel-Aviv - Hoffmann, Jeremie; Nevo-Goldberst, Hadas (Docomomo Journal, 2018)
This paper surveys the historical urban infrastructure and architecture of the School of Mechanical Engineering at Tel-Aviv University, designed by one of the greatest architects of the 20th century, Louis I. Kahn. The paper describes the monumental architecture of the building, which hints subtly to the qualities and complexity of the internal spaces. The structure is the only building ever erected in Israel by Kahn, and became an architectural icon, presenting the best in the Brutalist architectural style to be found in Tel-Aviv-Yafo, alongside other outstanding structures from the same period.